To study the prevalence of spontaneous abortions in pregnant women with hypothyroidism in the tertiary referral centre - Faisal, Shameel; Tibrewala, Satish; Afreen, Sana; Shetty, Raksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The thyroid diseases are the commonest endocrine disorders affecting women of reproductive age group maternal hypothyroidism is the most common disorder of thyroid function in pregnancy and has been associated with spontaneous pregnancy loss, pre eclampsia, preterm delivery, antepartum hemorrhage, low birth weight, fetal distress and reduced intellectual function of the offspring. The objective was to study the prevalence of spontaeous abortions in the pregnant women with hypothyroidism. Methods: All cohort cases were selected prospective from consecutive pregnant female attending the antenatal clinics of tertiary referral centre in study period of three years. FT3, FT4 and serum TSH were done in them and the results were compared Pregnancy specific reference ranges were also applied. The patients were divided into two groups based on time of hypothyroidism detection and diagnosis. The past history or prevalence of Spontaneous Abortions were compared in both the groups. Results: The prevalence of hypothyroidism was 5.6% in women routine antenatal clinic which was highly significant. The prevalence of spontaneous abortion in the past in the group A was 18% as compared to 28% in group B, difference being highly significant. Conclusions: Hypothyroidism is highly prevalent in patients who had obstetric repercussions. Early diagnosis and thyroxine replacement can prevent complications in the future pregnancies. Thyroid function tests should be included in the list of routine investigation done in an antenatal mother and should become a mandatory investigation in patients with previous adverse pregnancy outcomes.